The impact of municipal infrastructure grant on basic service delivery : a case of Elias Motsoaledi Local Municipality in Limpopo Province - Matabane, Gloria Semakaleng (University of Limpopo, 2017)
Municipalities support social and economic development through infrastructure investment and help to alleviate poverty by providing free basic services to the poor households. The primary funding mechanisms to support municipal service delivery to the poor is the MIG allocated to the municipalities in the form of conditional grant. The MIG programme was specifically established to assist the poor to gain access to infrastructure and can only be used for infrastructure towards basic services. This study investigates the impact of Municipal Infrastructure Grant (MIG) on basic service delivery in Elias Motsoaledi Local Municipality which is in Limpopo Province. The findings and recommendations are mainly and only applicable to this specific municipality although there may be areas of possible extrapolation. This study employed primarily a qualitative research as a methodological approach to address the specific research questions. The interview schedule and semi-structured questionnaire were used together with the examination of existing documents. A total of 28 municipal officials and community representatives were involved in this study. Data was analysis using qualitative content analysis method and descriptive statistics. The findings revealed that: Firstly, the finding highlights that the municipality makes all efforts to comply with the requirements of MIG. (a) The spending trend of the municipality shows effective utilization of MIG. However, records show that the municipality has a tendency of spending after three months (October) after commencement of the financial year (It should be noted that the municipal financial year starts from July to June of the next calendar year). The result also reveals that at the project level there might be some over spending tendencies. (b) It is also evident that the municipality has the capacity and the mechanisms to manage MIG implementation; nonetheless, there is a sign that there is inadequate capacity of technical administrative skills and project management skills which are essential for MIG administration. (c) Mechanisms to monitor MIG implementation are indicated by site visits, site meetings and monthly service provider meetings. (d) The municipality demonstrates iv accountability in terms of the administration of MIG by submission of monthly reports, annual reports; implementation plans; cash-flow budget to the national office through provincial office; and by submitting financial statements to Treasury. (e) There is an average understanding of knowledge of MIG and of decisions about projects budgets by community representatives. Secondly, although the finding reveals that the municipality is rendering basic services to its residents using the MIG, some officials indicated that there is a backlog in roads infrastructure and that the municipality needs more funding to address the backlog. The community representatives were recorded saying that the communities are not satisfied with the services rendered by the municipality. It was also evident that the municipality is struggling to address the backlog because of the mushrooming of new settlements and the limited MIG funds. Finally, the finding shows that MIG programme has contributed to improving basic service delivery in Elias Motsoaledi Local Municipality. Respondents from municipal office specified that MIG is the main source of funding for delivery of basic service to its communities. The community representatives revealed that they have benefited from different types of projects delivered by the municipality in their wards such as: water, sanitation, electricity, high mast lights, roads and storm water, community halls, crèches, sports facilities, parks, low level bridges and schools. It was also stated by community representatives that the infrastructural projects implemented are not properly maintained. In addition, the finding shows that most respondents are still not well-informed about MIG. That is the reason that they have inadequate information about the projects at local level. Keywords: Infrastructure; Grant; Service; Impact; Municipality
Thesis (M. Dev.) -- University of Limpopo, 2017.
Keywords: Municipality; Municipal service grants; Municipality infrastructure; Municipality -- South Africa; Municipal services -- Law and legislation